2010
DOI: 10.1128/aac.00150-10
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Posaconazole in Hematology Patients: Experience with a New High-Performance Liquid Chromatography-Based Method

Abstract: Parallel administration of the proton pump inhibitor (PPI) esomeprazole has been shown to decrease oral bioavailability of posaconazole in healthy volunteers. We prospectively analyzed serum samples (n ‫؍‬ 59) obtained from hematology patients (n ‫؍‬ 27) under posaconazole prophylaxis. Patients treated concomitantly with pantoprazole had significantly lower posaconazole levels than patients without PPI treatment (median levels of 630 g/liter versus 1,125 g/liter, respectively). These results suggest that drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…3A). In a cohort of 17 cardiothoracic transplant recipients, Shields and colleagues found significantly lower posaconazole concentrations in patients receiving proton pump inhibitors (37); a similar result was identified by Neubauer et al (31). Controlled studies in healthy volunteers have identified reductions in the area under the posaconazole concentration-time curve (AUC) of 32% (20) and 37% (41) with esomeprazole, with the later study also confirming the pH-dependent solubility (and absorption) of posaconazole through monitoring of intraluminal posaconazole concentrations (41).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…3A). In a cohort of 17 cardiothoracic transplant recipients, Shields and colleagues found significantly lower posaconazole concentrations in patients receiving proton pump inhibitors (37); a similar result was identified by Neubauer et al (31). Controlled studies in healthy volunteers have identified reductions in the area under the posaconazole concentration-time curve (AUC) of 32% (20) and 37% (41) with esomeprazole, with the later study also confirming the pH-dependent solubility (and absorption) of posaconazole through monitoring of intraluminal posaconazole concentrations (41).…”
Section: Discussionsupporting
confidence: 62%
“…Coadministration with food has been shown to increase posaconazole bioavailability by up to 4-fold (20); conversely, medications such as proton pump inhibitors have been shown to significantly decrease posaconazole exposure due to increased gastric pH (41). Low posaconazole concentrations have been commonly reported in clinical practice (3,10,23,31,37,39), with the current lack of an intravenous formulation of the drug complicating efforts to increase posaconazole exposure, particularly in critically ill patients (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although conflicting data on this topic still exist in the literature (14,27), it should be noticed that in a study assessing posaconazole exposure after standard dosages in relation to the use or nonuse of pantoprazole in hematological patients, significantly lower median C min values were reported for patients taking this PPI than for those who did not (630 and 1,125 ng/ml, respectively) (20).…”
Section: Discussionmentioning
confidence: 99%
“…C ss values of Ͻ500 ng/ml were reported in several cases with this regimen by various authors (in 79.6% of cases [16], in 76.2% of cases [17], and in 44% of cases [18]). Likewise, when considering the threshold of 700 ng/ml, even higher percentages of cases with subtherapeutic C ss values were reported (in 85.2% of cases [16], in 90.5% of cases [17], in 70.3% of cases [19], in 48% of cases [20], and in 20% of cases [21]). Of note, it should not be overlooked that most of those studies considered either patients taking posaconazole alone or those taking it concomitantly with PPIs or with H 2 antagonists (22), which are known to impair the posaconazole absorption rate.…”
Section: Discussionmentioning
confidence: 99%